2004
DOI: 10.1002/pola.20314
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene/1‐pentene copolymers synthesized using the metaloxycarbene complex catalyst system [(CO)5W=C(Me)OZr(Cp)2Cl]/MAO

Abstract: Ethylene/1-pentene copolymers were prepared using a [(CO) 5 Wϭ C(Me)OZr(Cp) 2 Cl] (1)/MAO catalyst system. 1-Pentene incorporation in the copolymer was monitored using 13 C-NMR spectroscopic methods. The weight average molecular weights (M w ) of the copolymers were between 142,000 and 629,000 g/mol, with polydispersity indexes (PDIs) ranging from Ϸ 2 to 90, as analyzed by size exclusion chromatography (SEC). Melting and crystallization temperatures, determined using differential scanning calorimetry (DSC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The signal assignments as shown in Fig. 1c are based on Randall [19] and others [20][21][22]. The copolymer compositions were calculated from the intensities of the branch carbon (br) and the backbone carbons (α, β, γ, δ, ε).…”
Section: Resultsmentioning
confidence: 99%
“…The signal assignments as shown in Fig. 1c are based on Randall [19] and others [20][21][22]. The copolymer compositions were calculated from the intensities of the branch carbon (br) and the backbone carbons (α, β, γ, δ, ε).…”
Section: Resultsmentioning
confidence: 99%
“…Since Cp 2 TiCl 2 was shown to polymerize ethylene when activated by methylaluminoxane, MAO (Sinn et al, 1980), derivatives of this compound have been synthesized where a Cl ligand was replaced by a monodentate anionic Fischertype carbene ligand (Barluenga and Fañanás, 2000). We have shown that zirconocene equivalents of this family of homogeneous catalysts, Cp 2 Zr(Cl)OC(R)M(CO) 5 (where M = W or Cr), catalyze the oligomerization of 1-pentene, as well as the copolymerization of ethene and 1-pentene, in the presence of MAO (Luruli et al, 2004;Luruli et al, 2006). Herein we report the crystal structure of the title zirconocene complex, (I).…”
Section: Data Collectionmentioning
confidence: 99%
“…For related literature regarding catalytic data of the title compound, see: Sinn et al (1980); Luruli et al (2004Luruli et al ( , 2006. For other cases of anionic Fischer-type carbenes being used as monodentate ligands, see: Barluenga & Fañ aná s (2000).…”
Section: Related Literaturementioning
confidence: 99%
“…For related literature regarding catalytic data of the title compound, see: Sinn et al (1980);Brü ll et al (2001); Luruli et al (2004Luruli et al ( , 2006. For comparable structures, see: Erker et al (1989); Wolczanski et al (1983); Esterhuysen et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…In our ongoing studies into finding improved catalysts for the oligomerization of αolefins we have studied zirconocene equivalents to (I) where we replaced one of the Cl ligands with a number of different ligands (Brüll et al, 2001). In particular, the use of a tungsten-carbene moiety as a ligand, (II), has been proven to result in an effective catalyst for the oligomerization of 1-pentene, as well as the copolymerization of ethene and 1-pentene, in the presence of MAO (Luruli et al, 2004;Luruli et al, 2006). Herein we report the crystal structure of the title zirconocene complex, (II).…”
Section: Data Collectionmentioning
confidence: 99%